Diversity of clinical, radiographic and genealogical findings in 41 families with amelogenesis imperfecta - Daniela Adorno-Farias; Ana Ortega-Pinto; Paulina Gajardo; Ana Salazar; Irene Morales-Bozo; Fabiola Werlinger; Sandra Rojas-Flores; Alfredo Molina-Berríos; Sonia Echeverría-López; José Jara-Sandoval; Lilian Jara; Blanca Urzúa (University of São Paulo, 2019)
Abstract Amelogenesis imperfecta (AI) is a group of enamel development disorders that alter the structure and chemical composition of the tissue. There is great variability in the clinical presentation; according to Witkop, AI can be categorized into 14 subtypes, which makes its diagnosis extremely complex. Objective: This study aimed to describe and determine the frequency of clinical and radiographic features and inheritance patterns found in 41 Chilean families diagnosed with diverse types of AI. Material and Methods: We analyzed the clinical records, photographs, pedigrees and radiographs of 121 individuals recruited between 2003 and 2016. All of the information was included in a database that was analyzed using the application Stata 14. Results: The 72 affected individuals had average age of 16 years, and no sex association with the presence of AI was found. The most frequent clinical subtypes were as follows: 43% hypomature, 25% hypoplastic, 21% hypomature/hypoplastic, 7% hypocalcified and 4% hypocalcified/hypoplastic. The number of severely affected teeth was 22, which occurred in the patients with hypocalcified and hypocalcified/hypoplasic AI who presented the highest number of damaged teeth. Caries and periodontal disease were found in 47 and 32% of the patients, respectively. Malocclusions were observed in 43% of the individuals with AI, with open bite being the most frequent. Radiographically, the thickness of the enamel decreased in 51% of the patients, and 80% showed decreased radiopacity of the enamel compared to that of dentin. Autosomal dominant inheritance pattern was found in 37% of the families with hypoplastic AI, and autosomal recessive pattern was present in 56% of the other clinical subtypes, but more frequently in those affected with hypomature and hypocalcified AI. Conclusion: Of the five clinical subtypes, autosomal recessive hypomature, autosomal dominant hypoplastic and autosomal recessive hypomature/hypoplastic AI were the most prevalent subtypes in this group.